Analisis Usability Website Si-Prestasi Dengan Metode USE Questionare - Agus Dwi Milniadi; Yudha Alif Auliya (Faculty of Computer Science, University of Jember, 2021)
Web technology is growing rapidly, with today's website being a role to improve effectiveness, the design of the web can be said to be good when it meets usability aspects for testing the products, which are compatible with the manufacturing and easier access to the site. One of the implementations of the effectiveness of website technology is the implementation of the website to assist with learning teaching at the covid-19 pandemic. Nganjuk district will maintain it by creating an e-learning based website called Si-Prestasi. But in the user data found on the si-prestasi website, there is a user decline from the Si-Prestasi website. In January 2021, student users reached 731,621 and in April 2021 to 187,590 times and teacher users, 3,658 times opened the applications for their accomplishments, and in April 2021 down to 11,612 times. Thus the study aims to analyze Culinaire's usability system by referring to the 5 aspects of usability: learnability, efficiency, memorability, errors, and satisfaction. The results of this research demonstrate that the aspects of learnability, efficiency, memorability, and satisfaction are at a good category value and the error aspect falls insufficient category. Therefore, improvements need to be made to optimize the website and improve on the server si-prestasi websites.